A meta-analysis of online health adoption and the moderating effect of economic development level. (July 2019) - Zhao, Yang; Li, Kunlin; Zhang, Liyi
Highlights: This meta-analysis aims to obtain a unified conclusion about the online health adoption. 43 empirical articles including 46 studies are selected. All of the model's path relationships are found support. The moderating effect of economic development level does have a special impact. This study has discussed the implications, research limitations and future directions. Abstract: Purpose: Due to the gradual transformation and upgrading of traditional medical industry, online health has become a hot spot recently. Various empirical researches have explored the critical factors that affect users' adoption behavior of online health, but their conclusions cannot be completely unified. Therefore, this paper aims at providing an integrated analysis, so as to explore the strength of the proposed online health adoption model's path relationship and the moderating effect of economic development level by dividing the sample into two subgroups, developed countries or areas and developing countries or areas. Design/methodology/approach: This paper conducted a meta-analysis by synthesizing the effect sizes extracted from a total of 43 articles including 46 empirical studies, which were searched from a variety of journals, conferences, book chapters and theses. Findings: Results show that all combined effect sizes of the proposed conceptual model are statistically significant and indicate that the users' adoption behavior of online health is mainly affected by perceived ease of use, perceived usefulness and subjective norm, rather than perceived behavioral control, innovativeness and trust. Furthermore, the moderator analysis confirms that the economic development level does have a moderating effect on the two relationships, perceived ease of use - perceived usefulness and innovativeness - behavioral intention. Specially, results manifest that the impact of perceived ease of use toward perceived usefulness receives more attention in developed countries or areas, while the impact of innovativeness toward behavioral intention is more noteworthy in developing counties or areas. Originality/value: This paper was conducted with the view of obtaining a unified conclusion about the research field of online health adoption. Its content is original. Whether in the academia or industry, the findings of this research will have implications for the future development of online health.